Optimising Inventory Control in Pharmaceutical Distribution: A Case Study on PT. XYZ - Foci, Nia Arfina; Indrapriyatna, Ahmad Syarfuddin (Performa: Media Ilmiah Teknik Industri, 2000)
Inventory control is a policy designed to manage and regulate the supply, storage, and accessibility of items in an organisation. Its primary purpose is to ensure that there is always enough stock on hand to meet demand while minimising the costs associated with holding and maintaining inventory. XYZ, a pharmaceutical distributor, faces challenges in optimising its inventory control policy, resulting in frequent stockouts, overstocks, and product damage during distribution. This study aims to design an optimised inventory control policy to enhance the Company's drug inventory system performance. The research begins by classifying inventory items using the ABC method and calculating the inventory turnover ratio (TOR). A scatter diagram is then constructed based on historical demand data to identify product demand patterns. Subsequently, three forecasting methods are applied, and the most accurate method is selected based on the Mean Absolute Percentage Error (MAPE). Inventory issues are categorised, with Class A drugs managed using the Q model and Classes B and C using the P model. The Hadley-Within method with backorder is employed for inventory problem-solving. The proposed inventory policy results in a total inventory cost of IDR 339,221,858 and a TOR of 4.26. In contrast, the existing system incurs a total inventory cost of IDR 1,338,286,901 with a TOR of 8.7. Implementing the optimised policy would lead to a cost reduction of 74.65%, equating to IDR 999,065,044, and improved inventory efficiency. This study provides a practical approach for pharmaceutical distributors to enhance inventory management, reduce costs, and optimise supply chain performance.